Childhood Onset Systemic Lupus Erythematosus with Direct Coombs Test Positive in the Absence of Hemolytic Anemia – A Rare Case Report - Sreekumar, Vani; ., Mangaiyarkarasi (Annals of Pathology and Laboratory Medicine, 2021)
Systemic Lupus Erythematosus being a chronic autoimmune multisystem inflammatory disease, affects predominantly women of reproductive age group. Childhood – Onset Systemic Lupus Erythematosus is a rare disease with an incidence of 10% - 20%. Positive direct Coombs test in the absence of hemolytic anemia indicates high disease activity and severe renal damage. Herein we report a case of 11-year-old female child diagnosed as Systemic Lupus Erythematosus with positive direct Coombs test in absence of hemolytic anemia which is very rare.